Singing with the foodies - Andrade, Débora (2023)
In this work, the book “Cantando com as comilanças” is described and analysed, from the point of view of his contributions to field of literature on children´s musical-vocal development. Thus, the compositional characteristics, as well as its vocal technical objectives are identified in the thirteen vocal exercises, created by Juliana Melleiro. They are: expand children´s vocal range, explore facial resonators, develop different zones of textual articulation and enable vocal flexibility.